2010
DOI: 10.3366/word.2010.0003
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic iconicity in the evaluative morphology of a sample of Indo-European, Niger-Congo and Austronesian languages

Abstract: Universals Archive (Universal #1926) indicates a universal tendency for sound symbolism in reference to the expression of diminutives and augmentatives. The research ( Štekauer et al. 2009 ) carried out on European languages has not proved the tendency at all. Therefore, our research was extended to cover three language families – Indo-European, Niger-Congo and Austronesian. A three-step analysis examining different aspects of phonetic symbolism was carried out on a core vocabulary of 35 lexical items. A resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…There seems to be a tendency for diminutives to contain high-frequency vowels and consonants, and augmentatives to contain low-frequency vowels, backed up by some cross-linguistic evidence (Ultan, 1978). Some studies suggest that no reliable associations can be found (Bauer, 1996;Gregová et al, 2010;Körtvélyessy, 2011), but the language samples used in these are rather small, including only a few language families, and the studies were aimed at testing a rather restrictive hypothesis of contrastive associations between high front vowels (and post-alveolar and palatal consonants) in diminutives on one side, and high back vowels in augmentatives on the other.…”
Section: Grammaticalized Vocal Iconicitymentioning
confidence: 99%
“…There seems to be a tendency for diminutives to contain high-frequency vowels and consonants, and augmentatives to contain low-frequency vowels, backed up by some cross-linguistic evidence (Ultan, 1978). Some studies suggest that no reliable associations can be found (Bauer, 1996;Gregová et al, 2010;Körtvélyessy, 2011), but the language samples used in these are rather small, including only a few language families, and the studies were aimed at testing a rather restrictive hypothesis of contrastive associations between high front vowels (and post-alveolar and palatal consonants) in diminutives on one side, and high back vowels in augmentatives on the other.…”
Section: Grammaticalized Vocal Iconicitymentioning
confidence: 99%
“…An experimental study also showed that 561 Featural affixation and sound symbolism in Fungwa English-speaking participants associated front vowels with positive brand names, whereas back vowels were associated with negative image branding (Lowrey & Shrum 2007). Other studies, based on more than twenty language samples, suggest that the link between evaluative morphology and sound symbolism is not universal, but language-or area-specific (Ultan 1978, Bauer 1996, Gregová et al 2010, Körtvélyessy & Stekauer 2011.…”
Section: Evaluative Formation and Sound Symbolismmentioning
confidence: 97%
“…Diminutive and augmentative are categories of evaluative morphology (Scalise 1984, Stump 1993, Bauer 1997. In natural languages, evaluative morphology is intertwined with phonetic iconicity or sound symbolism (Jespersen 1922, Gregová et al 2010. According to Plank & Filimonova's (1996, 2000 universals 1926 and 1001, diminutives tend to contain high front vowels, whereas augmentatives tend to contain back vowels.…”
Section: Evaluative Formation and Sound Symbolismmentioning
confidence: 99%
See 1 more Smart Citation